2012
DOI: 10.1159/000335955
|View full text |Cite
|
Sign up to set email alerts
|

The Gastrin-Releasing Peptide Receptor as a Marker of Dysplastic Alterations in Cervical Epithelial Cells

Abstract: Background: Cervical cancer is a leading cancer in women worldwide. The Papanicolaou test (Pap test) remains the main screening tool; however, it produces high rates of false-negative and false-positive results. Gastrin-releasing peptide is a growth factor that has been implicated in many cancers, and its main receptor, the gastrin-releasing peptide receptor (GRPR), is nearly always expressed in cervical dysplasias and invasive carcinomas. The aim of this study was to evaluate the diagnostic potential of GRPR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Akt: protein kinase B; ANOVA: analysis of variance; FSP-1: fibroblast-specific protein-1; GRPR: gastrin-releasing peptide receptor; mRNA: messenger RNA; NC: negative control; PI3K: phosphatidylinositol 3-kinase; RT-qPCR: reversetranscription quantitative polymerase chain reaction; SD: standard deviation; TEC: tubular epithelial cell the activation of the PI3K/Akt signaling pathway, thus suppressing the development of the EMT and formation of the calcium oxalate crystal in renal TECs.During our study, the results showed that GRPR via inhibiting the PI3K/Akt signaling pathway downregulates the development of EMT.GRPR belongs to the G-protein receptor superfamily and leads to cell proliferation and growth by the activation of several signal transduction pathways(Flores et al, 2010). The overexpression of GRPR is observed in many human malignant tumors, acting as a molecular target in the anticancer therapy(Cornelio, Meurer, Schwartsmann, & Roesler, 2012). The main feature of EMT is the transformation of tightly attached and cuboidal epithelial cells into unanchored and extended mesenchymal type cells, which exhibit actin reorganization, loss of epithelial cell adhesion, and increased cell migration and invasion in renal fibrosis(McMorrow, Gaffney, Slattery, Campbell, & Ryan, 2005).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Akt: protein kinase B; ANOVA: analysis of variance; FSP-1: fibroblast-specific protein-1; GRPR: gastrin-releasing peptide receptor; mRNA: messenger RNA; NC: negative control; PI3K: phosphatidylinositol 3-kinase; RT-qPCR: reversetranscription quantitative polymerase chain reaction; SD: standard deviation; TEC: tubular epithelial cell the activation of the PI3K/Akt signaling pathway, thus suppressing the development of the EMT and formation of the calcium oxalate crystal in renal TECs.During our study, the results showed that GRPR via inhibiting the PI3K/Akt signaling pathway downregulates the development of EMT.GRPR belongs to the G-protein receptor superfamily and leads to cell proliferation and growth by the activation of several signal transduction pathways(Flores et al, 2010). The overexpression of GRPR is observed in many human malignant tumors, acting as a molecular target in the anticancer therapy(Cornelio, Meurer, Schwartsmann, & Roesler, 2012). The main feature of EMT is the transformation of tightly attached and cuboidal epithelial cells into unanchored and extended mesenchymal type cells, which exhibit actin reorganization, loss of epithelial cell adhesion, and increased cell migration and invasion in renal fibrosis(McMorrow, Gaffney, Slattery, Campbell, & Ryan, 2005).…”
mentioning
confidence: 55%
“…GRPR belongs to the G-protein receptor superfamily and leads to cell proliferation and growth by the activation of several signal transduction pathways (Flores et al, 2010). The overexpression of GRPR is observed in many human malignant tumors, acting as a molecular target in the anticancer therapy (Cornelio, Meurer, Schwartsmann, & Roesler, 2012). The main feature of EMT is the transformation of tightly attached and cuboidal epithelial cells into unanchored and extended mesenchymal type cells, which exhibit actin reorganization, loss of epithelial cell adhesion, and increased cell migration and invasion in renal fibrosis (McMorrow, Gaffney, Slattery, Campbell, & Ryan, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…GRPR activation has been shown to stimulate cancer cell proliferation, whereas GRPR antagonists to reduce tumor growth in a range of experimental cancer models (1,2). In gynecologic cancers, GRPR is likely to be highly expressed in breast, ovarian and cervical tumors, as well as in breast cancer cell lines, whereas its expression is low or absent in non-neoplastic tissue and healthy cells (1,(3)(4)(5)(6)(7)(8). The pharmacological blockade of GRPR by synthetic peptides acting as selective antagonists (RC-3940-II, RC-3095) has been shown to reduce human breast and ovarian tumor growth xenografted into nude mice (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly targeted radiopharmaceuticals are being tested in a variety of oncologic settings ( 14 , 15 ). Because GRPR occurs and stimulates cell proliferation in uterine cervix cancer ( 7 9 ), radiopharmaceutical peptide–receptor cohesion might have a therapeutic value by bringing a cell-killing radionuclide directly to cancer cells. The 212 Pb-DOTAM-GRPR1 radiopharmaceutical is an α-particle-emitting radionuclide 212 Pb, a metal chelator DOTAM, and a GRPR-targeted antagonist that is currently being studied in the metastatic uterine cervix cancer setting (NCT05283330) as well as in a variety of other cancer types.…”
Section: Discussionmentioning
confidence: 99%